Cerebral Microbleeds in the Patients With Acute Stroke Symptoms - Heo, Sung Hyuk; Lee, Dongwhane; Kwon, Yong Chul; Kim, Bum Joon; Lee, Kyung Mi; Bushnell, Cheryl D.; Chang, Dae-IL (Frontiers in Neurology, 2018)
Background: Some patients with acute stroke symptoms do not show hyperintensities on diffusion-weighted image (DWI). A few case reports have indicated that acutely developed cerebral microbleeds (CMBs) might cause focal symptoms. This study sought to investigate the incidence and characteristics of symptomatic CMBs in the patients with acute stroke symptoms but without DWI ischemic lesions. Methods: We enrolled the patients with acute stroke symptoms who underwent magnetic resonance imaging including DWI and gradient echo (GRE) sequences within 7 days after symptom onset, at our prospective stroke registry. We then identified patients without DWI-positive ischemic lesions but with CMBs in the relevant brain regions. Results: Between January 2005 and February 2012, we identified 235 DWI-negative transient ischemic attack (n=221) and stroke (n=14) patients from 2129 consecutive patients at our registry. In total, 16 patients had CMBs corresponding to the focal symptoms. Among these 16 patients, 12 patients showed a hyperintense rim on DWI around a microbleed suspected to be related to focal symptoms; of the 12 patients, 7 experienced stroke symptoms for more than 24 hours. However, the symptoms in the remaining patients (5 patients with the hyperintense rim and 4 patients without the hyperintense rim) improved within 24 hours. Conclusion: Symptomatic microbleeds are infrequent but not rare in the patients with acute stroke symptoms. Perihematomal edema around an acute CMB can cause a hyperintense rim on DWI. Our results suggest that a combination of DWI and GRE imaging can help diagnose acute symptomatic CMBs.